Hexokinase 2 promoted cell motility and proliferation by activating Akt1/p-Akt1 in human ovarian cancer cells - Xueye Tian; Dan Liu; Xiaohang Zuo; Xiaoli Sun; Mengmin Wu; Xu Li; Yue Teng (BMC, 2022)
Abstract Background Recently, increasing evidence has indicated that elevation of Hexokinase 2 (HK2) plays an important role in several cancers on regulating cell motility and growth. However, its role on regulating cell EMT in human ovarian cancer still less to known. Methods The transwell and wound-healing assay were used to detect the effective of HK2 on regulating motility of ovarian cancer cells. Real Time PCR and Western Blotting were used to explore the changing of EMT-related proteins in HK2-modified cells. The clonogenic formation, cell growth curves and MTT assays were used to evaluate the effective of HK2 on regulating cell proliferation in HK2-modified cells. The flow cytometry was used to detect the differences in the distribution of cells in the cell cycle between the HK2-modified cells and their control cells. The correlation of HK2 and Akt1/p-Akt1 was explored by using Western Blotting, Akt1 inhibitor (MK2206) and transient transfection of an Akt1 recombinant plasmid. The potential correlation between HK2 and EMT-related proteins in human ovarian cancer tissues and OV (ovarian serous cystadenocarcinoma) was confirmed by using Pearson correlation analysis and TIMER 2.0. Results In ovarian cancer cells, overexpressing of HK2 enhanced cell motility by inducing of EMT-related proteins, such as CDH2, fibronectin, MMP9, ZEB1, ZEB2 and vimentin. Moreover, overexpressing of HK2 promoted cell growth by reducing p21 and p27 expression in ovarian cancer cells. Further studies demonstrated that this promotion of cell motility and growth by HK2 was probably a result of it activating of Akt1 (p-Akt1) in ovarian cancer cells. Additionally, the positive correlation between HK2 and p-Akt1, fibronectin, MMP9 expression in human ovarian cancer samples was verified by using Pearson correlation analysis. The positive correlation between HK2 and CDH2, fibronectin, MMP9, ZEB1, ZEB2 and vimentin in OV (ovarian serous cystadenocarcinoma) was confirmed by using TIMER 2.0. Conclusion This study demonstrated that HK2 could induce EMT-related proteins and reduce cell cycle inhibitor by activating Akt1 in human ovarian cancer cells, subsequently enhancing cell motility and growth, suggesting that HK2 participate in the malignant process of ovarian cancer by interacting with Akt1.